2002
DOI: 10.1034/j.1600-6143.2002.20612.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited Dose Monoclonal IL‐2R Antibody Induction Protocol after Primary Kidney Transplantation

Abstract: This study prospectively compared immunoprophylaxis with a single intraoperative dose (2 mg/kg) of monoclonal interleukin-2 receptor (IL-2R) antibody vs. noninduction in kidney transplant recipients treated with tacrolimus (FK 506), mycophenolate mofetil (MMF) and a prednisone-based immunosuppression regimen. One hundred recipients of first-kidney transplant were enrolled into the study to receive either anti-IL-2R monoclonal antibody, daclizumab (2 mg/kg intraoperatively, limited anti-IL-2R) or no induction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 30 publications
3
22
1
Order By: Relevance
“…We agree that the authors based their opinion on well-performed studies with historical maintenance immunosuppression and on large registry studies, which have many inherent weaknesses that prevent definitive conclusions. We also agree with the paucity of evidence regarding benefit for recipients with low immunologic risk over no induction; however, we would like to point out that Ahsan et al demonstrated fewer rejection episodes with IL2RA induction versus none in a randomized trial of low-risk kidney transplant recipients who received contemporary maintenance immunosuppression (2). Overall, we feel that the declarative statements made by the authors are not fully supported by the level of evidence that was cited.…”
contrasting
confidence: 38%
“…We agree that the authors based their opinion on well-performed studies with historical maintenance immunosuppression and on large registry studies, which have many inherent weaknesses that prevent definitive conclusions. We also agree with the paucity of evidence regarding benefit for recipients with low immunologic risk over no induction; however, we would like to point out that Ahsan et al demonstrated fewer rejection episodes with IL2RA induction versus none in a randomized trial of low-risk kidney transplant recipients who received contemporary maintenance immunosuppression (2). Overall, we feel that the declarative statements made by the authors are not fully supported by the level of evidence that was cited.…”
contrasting
confidence: 38%
“…Moreover, a subgroup analysis did not show difference in outcomes when cyclosporin and TAC maintenance regimens were compared. However, other prospective studies reported much lower rates of biopsy-proven rejection at 1 year (8%-15%) among kidney transplant recipients receiving IL2-RA induction and TAC/MPA/steroid maintenance (8,19,20). A recently published RCT with a 5-year follow-up (n=227) compared r-ATG with IL2-RA induction in high-risk DDRT recipients (mostly 75%-85% in each arm; maintained on TAC/MPA/steroid) (21).…”
Section: Steroid Maintenancementioning
confidence: 99%
“…In the era of TAC/MPA maintenance regimens with or without steroids, controversy exists with respect to the added benefit of IL2-RA induction therapy on outcomes of renal transplantation. In fact, there are recent data that support that no induction therapy could achieve acceptable acute rejection rates (#20% at 1 year after transplantation), with similar allograft and patient survival compared with IL2-RA induction in the setting of the TAC/MPA maintenance regimen (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Prospective randomized multicenter studies and retrospective registry analysis demonstrate that no-induction therapy can achieve acceptable acute rejection rates (10%-20% at 1 year after transplant), with allograft and patient survival similar to other induction modalities in living donor renal transplantation (LRT) (7)(8)(9)(10). However, the current Kidney Disease Improving Global Outcomes (KDIGO) Transplant Work Group guidelines recommend IL2-RA as a first-line induction agent in all types of donor-recipient profiles to reduce risk of acute rejection and allograft loss.…”
Section: Introductionmentioning
confidence: 99%